Plurilingualism in the new era: A conversation with Enrica Piccardo - Ortega, Yecid; Piccardo, Enrica (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The use of many languages has been around for many years; indigenous communities have used languages, dialects and variations of their languages to make meaning and share culture. Plurilingualism as a theory and educational approach looks at people’s language(s) repertories and how they use them at any given moment to communicate. In this interview with Dr. Enrica Piccardo, we discussed the concepts of plurilingualism and multilingualism as well as the importance for education and the advancement of a more ecological and synergic shift in paradigms in English teaching worldwide, and specifically in the LatinAmerican context.